Dendritic cell vaccines for high-grade gliomas - Eagles ME; Nassiri F; Badhiwala JH; Suppiah S; Almenawer SA; Zadeh G; Aldape KD (Dove Medical Press, 2018)
Matthew E Eagles,1 Farshad Nassiri,2,3 Jetan H Badhiwala,2 Suganth Suppiah,2 Saleh A Almenawer,4 Gelareh Zadeh,3,5 Kenneth D Aldape3,6 1Section of Neurosurgery, Department of Clinical Neurosciences, University of Calgary, Calgary, AB, Canada; 2Division of Neurosurgery, Department of Surgery, University of Toronto, Toronto, ON, Canada; 3MacFeeters-Hamilton Neuro-Oncology Program, University Health Network, Toronto, ON, Canada; 4Division of Neurosurgery, Department of Surgery, McMaster University, Hamilton, ON, Canada; 5Division of Neurosurgery, University Health Network, Toronto, ON, Canada; 6Division of Pathology, University Health Network, Toronto, ON, Canada Abstract: Glioblastoma (GBM) is the most common and fatal primary adult brain tumor. To date, various promising chemotherapeutic regimens have been trialed for use in GBM; however, temozolomide (TMZ) therapy remains the only US Food and Drug Administration-approved first-line chemotherapeutic option for newly diagnosed GBM. Despite maximal therapy with surgery and combined concurrent chemoradiation and adjuvant TMZ therapy, the median overall survival remains approximately 14 months. Given the failure of conventional chemotherapeutic strategies in GBM, there has been renewed interest in the role of immunotherapy in GBM. Dendritic cells are immune antigen-presenting cells that play a role in both the innate and adaptive immune system, thereby making them prime vehicles for immunotherapy via dendritic cell vaccinations (DCVs) in various cancers. There is great enthusiasm surrounding the use of DCVs for GBM with multiple ongoing trials. In this review, we comprehensively summarize the safety, efficacy, and quality of life results from 33 trials reporting on DCV for high-grade gliomas. Keywords: glioma, vaccine, dendritic cells, glioblastoma